ANALISIS PENGARUH SUKU BUNGA TERHADAP KREDIT USAHA MIKRO KECIL DAN MENENGAH (UMKM) PADA BANK PEMBANGUNAN DAERAH (BPD) DI PROVINSI JAMBI - Isnain Effendi (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
Monetary policy is one of wisdom that can affect a country’s economy, banking is a medium that limits between sector moneter with sectorial. Development of SME loans in  regional  development bank’s, the highest growth in 2008 at  41  % le diangka Rp. 5,197.687 M and  the lowest in  2011 with  growth  of  31  %  dianggka  Rp.  4.489.554 M  with  an average  growth of Smes given BPD  Jambi  Province amounted to  17,22  %, from  the  regression  resultsw are  negative  and  significant  impact  on  the  interest  rate  credit.    Keyword : the influence of interest rates, UMKM, the development of the area of jambi province